Aristotle and Cyprus - Hornblower, Simon (Classica et Mediaevalia, 2026)
(1) I begin with a tribute to Mogens Herman Hansen, most of which seeks to clarify his opinion about when the polis came to an end and, more important, when he believed it did not. It will refer mainly but not only to his Introduction to the Copenhagen Inventory. (2) This section offers, against recent criticisms, a defence of the Inventory’s treatment of Cyprus in the chapter by F.G. Maier. The section concludes with remarks about the poet Lykophron’s important Cypriot material, and argues for its relevance to the modern debate about the nature of the Cypriot poleis. (3) This short section introduces the main part of the article. Plato’s alleged attempts to make philosophers out of Sicilian rulers have been much discussed, and his pupil Aristotle was Alexander’s teacher. But the young Aristotle had less famous educational contacts with a prince of Cyprus. (4) Cyprus as an entity does not feature in Aristotle’s Politics; there is only a melodramatic allusion to the murder of the Cypriot king Evagoras I (of Salamis). But Aristotle or a member of his school wrote a – now almost totally mostly lost – Constitution of the Cypriots. One of the three probable fragments concerns the family of Nikokles king of Paphos. (5) One of Aristotle’s earliest works, 353 BCE (?), was the – Isokratean rather than Platonic – Protreptikos or Exhortation (to philosophy), now fragmentary, but influential in antiquity. It was addressed to ‘Themison prince of Cypriots’, who is otherwise unknown, as is his home city. This section speculates that Philip II of Macedon knew of and remembered this relationship later, when he invited Aristotle to teach his son Alexander, born in 356. (6) Aristotle’s equally early and fragmentary Eudemos or On the Soul (late 350s?) takes its name from a Cypriot philosopher-friend of Dion, who with other named philosophers had died fighting for Dion at Syracuse in 353 (Plut. Dio 22.5; the death is narrated proleptically). A dream-story in Cicero (Div. 1.53) provides another link with Philip II’s Macedon (cf. §5 above): Eudemos was on his way there in 358.